“A good deal about California does not, on its own preferred terms, add up”: Joan Didion between Dawning Apocalypse and Retrogressive Utopia - Eva-Sabine Zehelein (European Journal of American Studies)
Joan Didion’s depiction of the American West and California is colored by an idiosyncratic sensitivity to her surroundings, intertwined with a sentimental-retrogressive image of the nature, history, character, and meaning of the West as a cultural topos. Her New Journalism-like observations of California are always closely linked to her own self and psyche, are seismographs of her own confusions, of moments of disorientation, insecurity, and loss. Didion is therefore one of those exceptional writers, who, in her fictionalized reportages, comments on American reality, ideas, and her own predicament. Identity and landscape fuse into an auto-psychoanalysis, which at the same time reveals a great deal about the American condition, its constantly strained relationship between rhetoric or auto-mythology and lived reality. This article draws primarily on Slouching Towards Bethlehem (1968) and Where I Was From (2003), but also on After Henry (1992) and The White Album (1979), to illustrate these points.